Cluster analysis for corpus linguistics - Moisl, Hermann, 1949- (Quantitative linguistics ;, 2015)
The rapidly growing volume of digital natural language text and the complexity of data abstracted from it have increasingly rendered traditional corpus linguistic analytical methodology obsolete. This book describes a cluster analytic methodology for generating linguistic hypotheses on the basis of data abstracted from language corpora.